2018
DOI: 10.1001/jamacardio.2018.2288
|View full text |Cite
|
Sign up to set email alerts
|

Association of Left Ventricular Global Longitudinal Strain With Asymptomatic Severe Aortic Stenosis

Abstract: Subclinical myocardial dysfunction that is characterized by impaired LV GLS is often present in patients with asymptomatic severe AS with preserved LVEF. Left ventricular global longitudinal strain further deteriorates over time and impaired LV GLS at baseline is associated with an increased risk for progression to the symptomatic stage and the need for aortic valve intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
94
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(105 citation statements)
references
References 42 publications
7
94
1
3
Order By: Relevance
“…Therefore, 3-dimensional (3D) speckletracking echocardiography could provide a more precise representation of myocardial deformation [12]. New insights into LV remodeling and myocardial deformation could potentially improve our ability to identify patients with aortic stenosis who are at highest risk for adverse remodeling or early LV dysfunction [13][14][15][16][17][18]. However, few studies have comprehensively characterized myocardial deformation in patients with severe aortic stenosis by 3D speckle-tracking echocardiography [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, 3-dimensional (3D) speckletracking echocardiography could provide a more precise representation of myocardial deformation [12]. New insights into LV remodeling and myocardial deformation could potentially improve our ability to identify patients with aortic stenosis who are at highest risk for adverse remodeling or early LV dysfunction [13][14][15][16][17][18]. However, few studies have comprehensively characterized myocardial deformation in patients with severe aortic stenosis by 3D speckle-tracking echocardiography [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…5 Studies in patients with asymptomatic AS have demonstrated that subclinical LV dysfunction can be reliably identified by deformation imaging. [6][7][8][9][10] Resting global longitudinal strain (GLS) and basal longitudinal strain (BLS) are significant independent predictors of outcomes in patients with significant AS. Increased mechanical dispersion was shown to be a prognostic predictor in patients with severe AS with and without intervention.…”
mentioning
confidence: 99%
“…Unfortunately, the occurrence of low LVEF (<50%) in the absence of symptoms in severe AS is very rare (0.4%) (36). Irrespective of symptomatic status, patients with severe AS may have a subclinical left ventricular dysfunction determined by a decreased LV-GLS value (37). Recent studies suggested that even patients with LVEF value between 50% and 59% had unfavorable postoperative outcome compared to patients with LVEF value more than 60% (36).…”
Section: B) Lv-gls In Aortic Stenosismentioning
confidence: 99%